(untitled) (Bangladesh Heart Journal, 2021)
Background: There is no consensus on the role of beating heart coronary artery bypass graft surgery (BECAB) in adult Bangladeshi patients requiring coronary revascularization surgery. We aimed to conduct a systematic review on all literature related to BECAB and/or conventional (CCAB) to determine the comparability of the patient outcomes of BECAB with that of a controlled cohort. Method: We carried out a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. A meta-analysis was conducted to compare clinical outcomes between the BECAB and CCAB cohorts. Pooled analyses were also performed to determine the incidence rates of any adverse outcomes related to CABG. Results: We observed significantly lower rates of operation time (MD: -52.30, CI: -67.73 to -36.86, p<0.0001), ventilation time (MD: -8.64, CI: -9.47 to -7.82, p<0.0001) and ICU stay (MD: -17.47, CI: -33.57 to -1.38, p=0.03) associated with BECAB. From our pooled analyses of the BECAB cohort, we observed that the average blood loss was 500.303 [352.099, 648.507], while the average rates of perioperative MI (0.020 [0.002, 0.049]), stroke/TIA (0.015 [0.000, 0.042]), AKI (0.006 [0.002, 0.012]), respiratory complications (0.020 [0.000, 0.058]) and low output syndrome (0.123 [0.106, 0.141]) were all lower than the averages observed in the CCAB cohort. Conclusion: In an adult Bangladeshi CABG population, the clinical outcomes of patients that underwent BECAB were non-inferior to, if not better than, patients who underwent CCAB. Bangladesh Heart Journal 2020; 35(2) : 87-99